'IF I FEEL LIKE THIS, HOW DOES THE CHILD FEEL?' CHILD PROTECTION WORKERS, SUPERVISION, MANAGEMENT AND ORGANISATIONAL RESPONSES TO PARENTAL VIOLENCE. Issue 1 (2nd January 2016) - Hunt, Susan; Goddard, Chris; Cooper, Judy; Littlechild, Brian; Wild, Jim
Abstract : This study analysed workers' experiences of supervision following interactions with hostile and intimidating parents. This analysis examined management and organisational responses to worker stress, and assessed the adequacy of support that workers received. An online survey was designed to collect data on workers' experiences and free text responses were qualitatively analysed for references to the supervision they received in response to working with parents. 590 participants responded to the survey. 402 were qualified social workers, and 423 worked in child protection. Participants had experienced a range of violent behaviour from parents. The overwhelming theme in responses was the lack of support and supervision workers received, often in stressful and frightening circumstances. Approximately one quarter of participants only used organisational procedures, guidelines or protocols on dealing with hostile parents. Workers reported that mismanaged parental hostility affected their practice and the quality of protection that children received. The violence experienced had a significant negative impact on their personal and professional lives. Organisational responses in the form of supervision and education were often inadequate and resulted in children receiving reduced quality of protection. Recommendations for policy and practice change are discussed, with the aim of caring for workers and the children they protect.